Plasma levels of N-telopeptide of Type I collagen in periodontal health, disease and after treatment - Ganganna Aruna (Wolters Kluwer Medknow Publications, 2016)
Background: To determine plasma concentrations of bone resorption marker cross-linked N-terminal telopeptide (NTx) of Type I collagen in periodontal health, disease and after nonsurgical periodontal therapy in chronic periodontitis group.In addition, to know the association between plasma NTx levels and the different clinical parameters. Materials and Methods: Thirty subjects were divided on the basis of their periodontal status and were categorized as Group I: Healthy, Group II: Gingivitis, and Group III: Chronic periodontitis. Group III subjects were treated with scaling and root planing, 6-8 weeks later blood samples were analyzed, and they constituted Group IV. NTx levels in plasma were analyzed by competitive - enzyme-linked immunosorbent assay. All data were analyzed using statistical software (SPSS) (α = 0.05). Results: All the samples tested positive for the presence of NTx. The mean NTx concentration was highest in Group III (18.77 nanomole Bone Collagen Equivalent [nm BCE]) and the lowest in Group IV (16.02 nm BCE). The values of Group I and Group II fell between the highest and the lowest values (16.23 nm BCE and 16.70 nm BCE, respectively).The difference in mean NTx levels in Group III and Group IV were statistically significant. NTx levels in all the groups positively correlated with the clinical parameters. All data were analyzed using statistical software (SPSS) (α = 0.05). Conclusion: Within the limits of this study, it may be suggested that plasma NTx levels may provide distinguishing data between periodontally healthy diseased sites and after nonsurgical therapy of diseased sites.